UJI PENDAHULUAN SIFAT FISIKA MEKANIKA PAPAN PARTIKEL KAYU KAWUI (Vernonia arborea) DENGAN TIGA PERSENTASE PEREKAT PVac (Polyvinyl acetate) - Lies Indrayanti; Grace Siska; Frankie Sijabat (Agrienvi: Jurnal Ilmu Pertanian, 2023)
The purpose of the study was to determine the quality of Kawui wood particle board using PVac adhesive. The study used Kawui sawdust material size 10 mesh. The study design used a complete randomized design. The treatment used is 7%, 11% and 15% adhesive percentages. The test parameters of the physical properties of particle board mechanics include moisture content, water absorption density, thickness development, modulus of elasticity, modulus of rupture, internal bond and screw unplug firmness. The results showed that different PVAc adhesive levels did not have a significant effect on the physical properties of particle board, namely moisture content, density, thickness development, and water absorption. In the mechanical properties of adhesive content has a significant effect on the mechanical properties of wood particle board kawui, namely (Internal Bond / IB and Screw Unplug Constancy except for the Modulus of elasticity (MoE) and modulus of rupture (MoR), the Physical Properties of the resulting particle board do not meet SNI 03-2105-2006 standards, namely for the parameters of Water Content, Density, Water Absorption unless the Thickness Development meets the standards. The mechanical properties of particle boards, namely Modulus of fracture (MoR), Internal Bond (IB), Firmness of Screw Pull are not included in these standards. The condition of the results of this study is thought to be caused by the lack of adhesive percentage and uneven distribution of adhesives.